In the Shadow of Mosquitoes: Analysis of Malaria Burden in India using Citation Network - Sharma, Yash Paul; Sindhania, Ankita; Waliya, Rohan Ranjan; Murmu, Cornelius; Roy, Kareena (Information Research Communications, 2026)
Background Malaria, with its deep historical roots in human civilization, stands as a testament to the enduring challenges posed by infectious diseases. This paper embarks on a journey through the historical context of malaria, tracing all publications from its evolution and impact on societies worldwide. Objectives/Purpose Leveraging bibliographic citation network analysis, this study explores the trajectory of malaria research in India from 1900 to 2024. Methodology Drawing upon a dataset of 2045 articles sourced from the Web of Science database, the study employs VOSviewer software to analyze publication trends, citation patterns, collaborative networks, and keyword associations. Results Results indicate a substantial increase in both publication volume and citations over the 124 years, reflecting evolving efforts to understand and combat malaria. A total of two thousand forty-five (n=2045) with a citation score of 34762, h-index of 72, and contributed by 6492 authors from 89 countries. India emerges as a focal point, accounting for over 85% of publications, underscoring the country's significant burden of malaria. Collaborative networks among researchers, spanning across countries and disciplines, underscore the global effort to address this public health challenge. Conclusion/Implications Specialized journals, such as the Malaria Journal, play a pivotal role in disseminating research findings and shaping discourse on malaria.
Keywords: Anopheles; Citation Network Analysis (CNA); Malaria; Plasmodium falciparum; Plasmodium vivax.